Analisa Legalitas Serangan Drone Asing Berdasarkan Hukum internasional : Studi Kasus: Indonesia - Giska Fajari; Irwan Triadi (Jurnal Hukum dan Sosial Politik, 2025)
Drones are a new technology that can pose a threat to the sovereignty of many countries. Therefore, preventive efforts are necessary for a government to safeguard its interests. In this context, Indonesia needs to establish a legal framework from an international legal perspective, supported by national positive law, to mitigate the use of drones. The research, conducted through a normative-judicial analysis approach, concludes that a considerable number of legal instruments are aimed at protecting Indonesia from drone threats. However, Indonesia's military capability is not yet fully equipped to enforce the mandates of these laws. Consequently, the approach that can be taken is to prohibit drones altogether because they violate human rights and harm society.